Studies on Homalomeneae (Araceae) of Borneo VIII: Delimitation of additional informal suprageneric taxa for Sundaic Homalomena - Ng Kiaw, Kiaw; Sofiman, Othman; Boyce, P.C; Wong, Sin Yeng (International Aroid Society Inc., 2011)
One new informal Supergroup and eight informal species' Complexes are proposed for Sundaic Homalomena (Araceae: Homalomeneae). Defining characters are enumerated and illustrated, and keys to all informal groups provided.